THE EFFECTIVENESS OF LEGAL PROTECTION FOR CHILDREN VICTIMS OF SEXUAL VIOLENCE AFTER THE ENACTMENT OF LAW NUMBER 12 OF 2022 CONCERNING THE CRIME OF SEXUAL VIOLENCE - Muhammad Ansori Lubis; Yusuf Hanafi Pasaribu; Syawal Amry Siregar (LPPM YPITI, 2026)
Sexual violence against children is one of the most damaging forms of human rights violations for the future of the nation's generations, and the number of cases in Indonesia does not show a significant downward trend even though the country has special legal instruments. The ratification of Law Number 12 of 2022 concerning the Crime of Sexual Violence (TPKS Law) is expected to be a legal breakthrough that fills the regulatory gap regarding the prevention, handling, protection, and recovery of victims, especially children. This article aims to examine the extent to which the TPKS Law is effective in protecting child victims of sexual violence in the first three years of its implementation (2022-2025), by examining the gap between normative-juridical protection and factually felt by victims in the field. This study uses a normative juridical method with a statute approach and a conceptual approach, supported by a literature study on official data from state institutions as well as national and international literature for the last five years. The results of the study show that the TPKS Law has normatively expanded the definition of sexual violence, introduced a mechanism for mandatory restitution, psychological assistance, and the establishment of a Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA), but its implementation is still hampered by the lack of implementing regulations in the early days, limited capacity of law enforcement officials, and the low ratio of cases that continue to the judicial process. The issuance of Government Regulation Number 30 of 2025 as an implementing regulation is also studied as an indicator of strengthening the effectiveness of advanced legislation. The novelty of this research lies in the synthesis of cross-year data trends (2022-2025) that have not been found in previous studies which are generally based on single-decision studies, resulting in a longitudinal and contextual map of legal effectiveness on the condition of child victims in Indonesia. This article recommends accelerating the harmonization of implementing regulations at the regional level and strengthening institutional capacity as a prerequisite for the effectiveness of the TPKS Law as a whole.